Peripheral nerve stimulator improves efficacy of the proximal paravertebral block in sheep - Costa, I. M. [UNESP]; Oliveira, M. A.; Floriano, B. P.; Abimussi, C. J. X. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2024)
The purpose of this study was to compare the efficacy of proximal paravertebral anesthesia in sheep using a peripheral nerve stimulator and compare it to the Cambridge technique. Eight Santa In & ecirc;s sheep, five females and three males aged 2 years and weighing 13kg were enrolled in the study. Right proximal paravertebral anesthesia was carried out using 2% lidocaine without vasoconstrictor, injected in the spaces between T13 -L1, L1 -L2 and L2 -L3, with and without the aid of a peripheral nerve stimulator in two procedures with an interval of 7 days between treatments, which comprised: ST (stimulator treatment: 3mg kg -1 of lidocaine 2%) and CT (Cambridge control treatment, 6mg kg -1 of lidocaine 2%). Cardiorespiratory variables were recorded before the treatment (baseline, T B ) and then at 15, 30, 45 and 60 minutes (T 15 , T 30 , T 45 and T 60 , respectively) following local anesthesia. Effectiveness of the regional anesthesia was assessed by means of mechanical skin clamping at a point between the iliac crest and the lowest border of the last rib. Data were tested for normal distribution using the Shapiro -Wilk test and compared using Kruskal-Wallis followed by Dunn post -hoc test. Duration of the blockade was analyzed using a Kaplan -Meyer survival curve. Analyses were performed under 5% significance. ST took significantly longer and had greater success and greater duration. Positive response to skin clamping in CT was obtained in seven animals at T 15 and one at T 45 , whereas in ST, one animal responded to skin clamping at T 15 , two at T 30 , four at T 45 and one at T 60 . Duration was significantly longer in ST compared to CT according to the Kaplan -Meyer analysis. No changes were seen in cardiorespiratory variables throughout the study. In conclusion, the peripheral nerve stimulator increases the success of proximal paravertebral anesthesia using a lower dose of 2% lidocaine in healthy sheep.
Keywords: regional anesthesia; large animals; ruminant; lidocaine